English Language Teaching (ELT) for Special Needs Learners: Strategies for Visually Impairments Students in Inclusive Education - Fitria, Tira Nur (English Edu: Journal of English Teaching and Learning, 2025)
This research describes English Language Teaching (ELT) for special needs learners for visually impaired students. This study employs a library research method. English Language Teaching (ELT) for visually impaired students (VIS) requires adaptive strategies to ensure an inclusive and effective learning experience. Key approaches include using Braille for literacy, multisensory learning with tactile objects and audio aids, and assistive technologies like screen readers and speech recognition apps. Emphasizing oral and auditory learning through role-playing, podcasts, and verbal exercises strengthens language skills. Structured instructions, adapted materials, and an inclusive environment foster engagement and accessibility. Encouraging independent learning with audiobooks and self-learning apps, building confidence through positive reinforcement, and promoting real-life applications help VIS students integrate English into daily life. Despite these strategies, teaching English to VIS students presents challenges such as a lack of teacher training, insufficient resources, and the absence of inclusive curricula. Limited vocabulary, longer learning times, and difficulties with activities requiring visual input make traditional methods ineffective. Classroom distractions, low motivation, and family support gaps further complicate learning. Teachers also face challenges in time management, student behavior, and classroom diversity, while Braille proficiency and system limitations add to these difficulties. To address these issues, educators must integrate specialized teaching techniques, including Total Physical Response (TPR), peer-assisted learning, and structured activities like dictation and role-playing. Classroom modifications, such as flexible seating and inclusive testing methods, enhance learning outcomes. By adopting an inclusive, multisensory approach and leveraging technology, teachers can create a supportive learning environment for VIS students. With the right strategies, resources, and teacher training, visually impaired learners can develop strong English skills, gain confidence, and participate fully in academic and social settings.